2022
DOI: 10.3389/fimmu.2022.946428
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Proteins and Peptides in Avian Eggshell: Structural Diversity and Potential Roles in Biomineralization

Abstract: The calcitic avian eggshell provides physical protection for the embryo during its development, but also regulates water and gaseous exchange, and is a calcium source for bone mineralization. The calcified eggshell has been extensively investigated in the chicken. It is characterized by an inventory of more than 900 matrix proteins. In addition to proteins involved in shell mineralization and regulation of its microstructure, the shell also contains numerous antimicrobial proteins and peptides (AMPPs) includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 206 publications
0
6
0
1
Order By: Relevance
“…45,46 Considering the glycosylation of OVT in various parts of the egg along with its antimicrobial properties, the Nglycan chain may play an important role in the structural stability and function of OVT. 47,48 Two possible mechanisms by which glycosylation increased the antibacterial activity of OVT are an increased ratio of β-sheets and β-turns, resulting in a stabler structure, and reduced hydrophobic residue contents, thereby increasing its solubility. 44 Aside from competing with bacteria for iron, OVT elicits additional antimicrobial properties by interacting with bacterial cell membranes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,46 Considering the glycosylation of OVT in various parts of the egg along with its antimicrobial properties, the Nglycan chain may play an important role in the structural stability and function of OVT. 47,48 Two possible mechanisms by which glycosylation increased the antibacterial activity of OVT are an increased ratio of β-sheets and β-turns, resulting in a stabler structure, and reduced hydrophobic residue contents, thereby increasing its solubility. 44 Aside from competing with bacteria for iron, OVT elicits additional antimicrobial properties by interacting with bacterial cell membranes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, OVT is one of the antimicrobial components in the ECL . Moreover, previous studies that employed nuclear magnetic resonance spectroscopy demonstrated that OVT-linked carbohydrate chains do not contain galactose and sialic acid, which is distinct from the glycosylation of serum transferrin. , Considering the glycosylation of OVT in various parts of the egg along with its antimicrobial properties, the N -glycan chain may play an important role in the structural stability and function of OVT. , Two possible mechanisms by which glycosylation increased the antibacterial activity of OVT are an increased ratio of β-sheets and β-turns, resulting in a stabler structure, and reduced hydrophobic residue contents, thereby increasing its solubility . Aside from competing with bacteria for iron, OVT elicits additional antimicrobial properties by interacting with bacterial cell membranes. ,, …”
Section: Resultsmentioning
confidence: 99%
“…( Marie et al, 2015b ). Lysozyme C, in addition to its antibacterial defense role, has been suggested to play a role in eggshell biomineralization ( Moreau et al, 2022 ). Under in vitro conditions, high concentrations of LYZ have been shown to alter crystal morphology ( Hincke et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by the literature stating that the decomposition of volatile materials such as moisture or surface water and organic compounds occurs at the range of 30 • C to 400 • C. The loss of organic compounds is primarily due to the removal of a membrane adhered to the eggshell. This membrane consists of carbohydrates and proteins which are rich in organic matter [65][66][67]. Another endothermic fluctuation along with a sharp drop in mass of approximately −24.76 mg is observed at 849.82 • C which indicates the decomposition of CaCO 3 .…”
Section: Thermogravimetric Analysis and Differential Thermal Analysis...mentioning
confidence: 98%
“…The loss of organic compounds is primarily due to the removal of a membrane adhered to the eggshell. This membrane consists of carbohydrates and proteins which are rich in organic matter [65][66][67]. Another endothermic fluctuation along with a sharp drop in mass of approximately −24.76 mg is observed at 849.82 °C which indicates the decomposition of CaCO3.…”
Section: Thermogravimetric Analysis and Differential Thermal Analysis...mentioning
confidence: 99%